Comparative chemical properties and antioxidant activity of two types of pomegranate fermented vinegar - Boonsupa, Wilawan; Onputta, Kanittha; Ajduangdee, Woradech; Glaichid, Pantita; Pupaijitkul, Anintita; Richomrat, Thiraphon (Asia-Pacific Journal of Science and Technology, 2021)
This study was conducted to produce fermented vinegar from two types of pomegranate, namely Chinese and Indian cultivar. The aim of the present study was to examine the chemical properties of vinegar and its antioxidant activities. From the fermentation of wine for 9 days, Chinese pomegranate wine had 9.95 ± 0.28 percent of alcohol content. The highest antioxidant activities and total phenolic content observed for the wine produced from the Indian cultivar were 32.58 ± 0.68 mg/mL and 536.73 mg/L, respectively. Vinegar fermentation was operated by inoculating 10% (v/v) of Acetobacter pasteurianus into two pomegranate wines with their start alcohol content adjusted to 5% (v/v). The fermentation was proceeded for 15 days at 30 ºC and sampling was operated at 5-day intervals. It was remarked for all samples that the level of alcohol decreased continuously over the fermentation period, While the amount of acetic acid increased. At the end of the fermentation process, the fermented vinegar produced from the Chinese cultivar showed the highest level of acetic acid of 7.50 ± 0.21%. The highest antioxidant activities and total phenolic content observed for the vinegar produced from the Indian cultivar were 35.25 ± 0.90 mg/mL and 480.24 ± 28.82 mg/L, respectively. The 9-point hedonic scale showed that the vinegar produced from Indian pomegranate exhibited the highest overall acceptability (7.63 ± 1.24), which indicated the very much pleasant level of the vinegar preference of the consumers.